2016
DOI: 10.2298/vsp141111026s
|View full text |Cite
|
Sign up to set email alerts
|

Association between ambient air pollution, meteorological conditions and exacerbations of asthma and chronic obstructive pulmonary disease in adult citizens of the town of Smederevo

Abstract: Exposure to airborne particles in the town of Smederevo, mainly to PM₂.₅, and to low temperature may trigger asthma exacerbation requiring emergency care. The most vulnerable may be women and obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In patients with chronic obstructive pulmonary disease, the number of days with high levels of PM 2.5 per month was significantly associated with the total number of COPD exacerbation [26]. Luong et al showed that an increase in 10μg/m 3 of PM 2.5 was associated with an increase in the risk of respiratory admission of 2.2% on the same day of exposure [27].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with chronic obstructive pulmonary disease, the number of days with high levels of PM 2.5 per month was significantly associated with the total number of COPD exacerbation [26]. Luong et al showed that an increase in 10μg/m 3 of PM 2.5 was associated with an increase in the risk of respiratory admission of 2.2% on the same day of exposure [27].…”
Section: Discussionmentioning
confidence: 99%
“…The variable weather conditions as well as Particulate Matter (PM) can raise the risk to public health (11)(12)(13). Many studies suggested that the surface temperature extremes were the key environmental factors related to the incidence of stroke and cardiovascular diseases (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Various lung diseases, such as COPD, asthma, and lung cancer, are related to PM exposure 7779. COPD is a progressive disease causing abnormal inflammatory response by harmful particles or gas.…”
Section: Respiratory Disease Induced By Particulate Matter Exposurementioning
confidence: 99%